Factors associated with non-prescription of oral anticoagulant treatment in non-valvular atrial fibrillation patients with dementia: a CPRD–HES study. (2nd April 2020) - Besford, Megan; Graham, Sophie; Sammon, Cormac; Mehmud, Faisal; Allan, Victoria; Alikhan, Raza; Ramagopalan, Sreeram
Abstract: Dementia is a common comorbidity in patients with atrial fibrillation (AF) and treatment guidelines recommend oral anticoagulant (OAC) therapy for AF patients with dementia unless concordance cannot be ensured by the caregiver. Despite this, the literature reports a low prescribing of OAC treatment in these patients. This study investigated possible factors associated with non-prescribing of OAC treatment in dementia patients newly diagnosed with non-valvular atrial fibrillation (NVAF) at age ≥ 65 years between 2013 and 2017 using the Clinical Practice Research Datalink and Hospital Episodes Statistics databases. Of 1090 dementia patients newly diagnosed with NVAF, 693 (63.6%) patients did not have a prescription for an OAC in the year following their diagnosis. The likelihood of experiencing a thromboembolic event was high, with 97% of the population having a CHA2 DS2 -VASc score > 2; however, little difference in the presence of stroke risk factors was observed between the prescribed and non-prescribed groups. The presence of bleeding risk factors was high; only 28 (2.6%) of patients did not have a previous fall or a HAS-BLED bleeding risk factor. A history of falls [OR = 0.76, 95% confidence intervals (CIs) (0.58, 0.98)], previous major bleed [OR = 0.56, 95% CI (0.43, 0.73)] and care home residence [OR = 0.47, 95% CI (0.30, 0.74)] were associated with not having an OAC prescription. The results suggest that dementia patients with NVAF and certain risk bleeding risk factors are less likely to be prescribed an OAC. Further work is needed to establish possible relationships between bleeding risk factors and other potential drivers of OAC prescribing.